Statistics for Business and Economics / Eight Edition - Anderson David R.; Sweeney Dennis J; Williams Thomas A (South-Western Thomson Learning, 2002)
This book shows clearly how to apply statistical methods in practical business situations. Preface, Data and Statistics, Descriptive Statistics: Tabular and Graphical Methods, Descriptive Statistics: Numerical Methods, Introduction to Probability, Discrete Probability Distributions, Continuous Probability Distributions, Sampling and Sampling Distributions, Interval Estimation, Hypothesis Testing, Statistical Inference about Means and Proportions with Two Populations, Inferences about Population Variances, Test of Goodness of Fit and Independence, Analysis of Variance and Experimental Design, Simple Linear Regression, Multiple Regression, Regression Analysis: Model Building, Index Numbers, Forecasting, Nonparametric Methods, Statistical Methods for Quality Control, Sample Survey, References and Bibliography, Summation Notation, Answers to Even-Numbered Exercises, Solutions to Self-Test Exercises, Index.